2006
DOI: 10.1021/ac060084f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Carbohydrate Microarrays on Gold Surfaces:  Direct Attachment of Nonderivatized Oligosaccharides to Hydrazide-Modified Self-Assembled Monolayers

Abstract: This paper describes a new and simple microarray platform for presenting multiple nonderivatized oligosaccharides to protein targets, with utility for mapping carbohydrate-protein recognition events. The approach is based on the creation of a hydrazide-derivatized, self-assembled monolayer on a gold surface in a single or two-step procedure, for efficient and selectively oriented anchoring of oligosaccharide probes via their reducing ends, with detection using fluorescence detection of bound proteins. The bigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
109
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 34 publications
0
109
1
Order By: Relevance
“…[25][26][27] Indeed, in our previous studies, we demonstrated that glycoarrays can be prepared by using hydrazide-modified surfaces on which nonspecific binding is reduced by the use of PEG-aldehyde blocking agent. [28] However, surface characterisation of these arrays has not been performed. Therefore, a short-chain PEG with a reducing end to react with unreacted hydrazide was employed as a blocking agent (Figure 2).…”
Section: Covalent Coupling Of Peg-aldehyde On Unreacted Hydrazide Sitmentioning
confidence: 99%
“…[25][26][27] Indeed, in our previous studies, we demonstrated that glycoarrays can be prepared by using hydrazide-modified surfaces on which nonspecific binding is reduced by the use of PEG-aldehyde blocking agent. [28] However, surface characterisation of these arrays has not been performed. Therefore, a short-chain PEG with a reducing end to react with unreacted hydrazide was employed as a blocking agent (Figure 2).…”
Section: Covalent Coupling Of Peg-aldehyde On Unreacted Hydrazide Sitmentioning
confidence: 99%
“…However, the glycan determinants recognized by individual GBPs are just beginning to be understood (Cummings, 2009), and is a major quest of modern glycomics research. The exploration of GBP interactions with glycans on microarrays of defined glycan structures represents a high-throughput method for exploring glycan-binding specificities (Blixt et al, 2004;Feizi and Chai, 2004;Fukui et al, 2002;Powell et al, 2009;Rillahan and Paulson, 2011;Song et al, 2008Song et al, , 2009Tateno et al, 2008;Willats et al, 2002;Zhi et al, 2006). Such information is important in identifying potential ligands for a GBP and developing hypotheses about their roles in GBP function.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore investigators have made great efforts to devise the novel routes and materials which can directly attach the unmodified carbohydrates. Coupling the carbohydrates with the aromatic amino groups, 5 aminooxy groups 33,34 and hydrazide groups 33,35 by reductive amination or with the phthalimide chromophores 36,37 functionalized surfaces under photocatalysis were the two reported effective routes to achieve this goal. As the reductive amination can be easily operated and suitable for various reducing carbohydrates, it was preferred by a number of researchers.…”
Section: Introductionmentioning
confidence: 99%